Comparison of combination therapies in the management of locally advanced pancreatic cancer: Induction chemotherapy followed by irreversible electroporation vs radiofrequency ablation - Chaobin He; Jun Wang; Yu Zhang; Zhiyuan Cai; Xiaojun Lin; Shengping Li (Cancer Medicine)
Abstract Background Locally advanced pancreatic cancer (LAPC) remains a challenge for current treatments. Local destructive therapies, such as irreversible electroporation (IRE) and radiofrequency ablation (RFA), were used more and more frequently in the treatment of LAPC. Objective This study aimed to compare the efficacy of IRE with RFA in patients with LAPC. Methods From August 2015 to August 2017, 58 LAPC patients after IRE or RFA therapy, which was performed through open approach, were retrospectively reviewed. The survival outcomes after IRE (36 patients) and RFA (18 patients) were compared after propensity score matching (PSM) analysis. Results Before PSM analysis, IRE after the induction chemotherapy resulted in significant higher overall survival (OS) rates and progression‐free survival (PFS) rates to RFA (2‐year OS, 53.5% vs 30.8%, P = .013; 2‐year PFS, 28.4% vs 12.1%, P = .043). After PSM analysis, compared with RFA, the survival benefit of IRE was even more obvious, (2‐year OS, 53.5% vs 27.0%, P = .010; 2‐year PFS, 28.4% vs 6.4%, P = .018). For patients with tumor larger than 4 cm, IRE resulted in comparable OS and PFS between RFA and IRE while IRE also achieved better long‐term OS to RFA for those with tumor smaller than 4 cm. Multivariate analysis illustrated that IRE was a favorable prognostic factor in terms of OS and PFS in patients with LAPC. Conclusions IRE after induction chemotherapy is superior to RFA after induction chemotherapy for treating LAPC patients while these two therapies have comparable efficacy for tumors which were larger than 4 cm.